Institutional Logics or Agency Costs: The Influence of Corporate Governance Models on Business Group Restructuring in Emerging Economies - Chung, Chi-Nien; Luo, Xiaowei (Organization Science, 2008)
Business groups, the leading economic players in emerging economies, have responded to the market-oriented transition primarily through corporate restructuring. Agency theory predicts that acquisition and divestiture would serve the interests of dominant families and foreign investors in different ways. Further, dominant families, foreign investors from shareholder-based countries, and foreign investors from stakeholder-based countries each operate under distinct institutional logics of appropriate restructuring strategies. We test hypotheses about agency and institutional mechanisms using large business groups in Taiwan between 1986 and 1998 as our empirical example. We find that, consistent with both mechanisms, family-controlled business groups are less likely to divest of unrelated businesses. However, the institutional logics mechanism can better explain the relative lack of unrelated acquisition in family-controlled groups and the difference in divestiture between groups with more shareholder-based foreign investment and those with more stakeholder-based investment. Our study contributes to the neo-institutional perspective of corporate restructuring and strategic management in general by empirically separating the two mechanisms and examining organizational responses to conflicting institutional logics. Our study also adds to the understanding of business group restructuring in emerging economies.